Unveiling harlequin ichthyosis beyond the neonatal period: A case from North Sumatra, Indonesia - Manurung, Widya Gabriella; Paramita, Deryne Anggia; Nababan, Kristo Alberto (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2026)
Harlequin ichthyosis (HI) is a rare and life-threatening form of autosomal recessive congenital ichthyosis, typically diagnosed in the neonatal period due to its distinctive clinical features. We report a 7-year-old boy from North Sumatra, Indonesia, who survived well beyond infancy despite limited resources. He was born preterm at 35 weeks to consanguineous parents, with a history of a sibling who died in early infancy from a similar condition. The patient presented with ectropion, eclabium, underdeveloped ears, severe contractures, and generalized hyperkeratotic plaques with deep fissures. Clinical management focused on supportive dermatologic care, including twice-daily bathing, emollient application, topical antibiotics for erosions, and multidisciplinary referrals. Notably, the patient did not receive systemic retinoids or neonatal intensive care, yet the survival was achieved with minimal but consistent supportive measures. This case underscores the importance of early recognition of HI, the role of family history and consanguinity in clinical suspicion, and the potential for survival in resource-limited settings. It also highlights the profound psychosocial burden on affected families and emphasizes the need for genetic counselling to reduce recurrence in high-risk populations.